Infertile patients with inflammatory bowel disease have comparable in vitro fertilization clinical outcomes to the general infertile population. (2nd June 2020) - Hernandez-Nieto, Carlos; Sekhon, Lucky; Lee, Joseph; Gounko, Dmitry; Copperman, Alan; Sandler, Benjamin
Abstract: To assess clinical outcomes of females diagnosed with Inflammatory Bowel Disease (IBD) and infertility, which underwent in vitro fertilization (IVF) with preimplantation genetic testing for aneuploidy. (PGT-A). Retrospective cohort study comparing clinical outcomes of patients with Inflammatory bowel disease who underwent IVF with PGT-A with a subsequent euploid single embryo transfer (SET) against a matched control group. Thirty-eight patients with an IBD diagnosis were compared to 114 controls. There was no significant difference in cycle outcomes among IBD and Control cohorts [implantation rate (71.0% vs. 78.0% ( p = .68)], clinical pregnancy rate [50.0% vs. 60.5% ( p = .68)], live birth [62.9% vs. 73.0% ( p = .06)] multiple pregnancy rate [0% vs. 1.1% ( p = .25)] and clinical pregnancy loss rate [10.5% vs. 5.7% ( p = .54)]. An IBD diagnosis was not found to significantly modify the odds of implantation [adjusted OR = 0.6 (95% CI −1.2 to 0.8)]. Additionally, the odds of implantation in patients with IBD were not altered by having ulcerative colitis or Crohn's disease diagnosis. (OR = 0.4 95% CI 0.1–1.9). Patients diagnosed with IBD who undergo a SET have clinical outcomes comparable to the general infertile population. Patients and physicians can be reassured that an IBD diagnosis does not impair IVF treatment outcomes. SYNOPSIS: Infertile patients with inflammatory bowel disease who utilized a single, euploid blastocyst transfer had IVF success rates comparable to the general infertile population.